Lymphatic therapy by Godoy method in the treatment of dyspnea after COVID- 19: case report - PereiradeGodoy, JoseMaria; Pereira de Godoy, Lívia Maria (Medicni Perspektivi, 2022)
Despite all efforts, this disease has been a major cause of mortality as well as sequelae after the infectious event. Issues regarding an effective form of treatment for the virus have led to efforts focused on the acute manifestations of the disease. The aim of the present study is to describe the first observational result of the treatment of a pulmonary sequela of COVID-19 with important symptomatic limitations. One month ago, the patient contracted COVID-19 and was treated clinically, but the case progressed with important respiratory and physical limitations. An increase occurred in the lymphedema and the patient sought treatment. She would waken at night with dyspnea and was unable to walk more than a few steps or climb stairs. Intensive treatment of the lymphedema was proposed using the Godoy Method®. The Godoy method for reversing fibrosis was useful in improving dyspnea in a short period of time in a patient with sequelae resulting from COVID-19.